An Auditory Model based Strategy for Cochlear Implants - Nogueira, Waldo; Kátai, András; Harczos, Tamás; Klefenz, Frank Markus; Büchner, Andreas; Edler, Bernd (Annual International Conference of the IEEE Engineering in Medicine and Biology Society EMBC, 2007)
A physiological and computational model of the human auditory system has been fitted in a signal processing strategy for cochlear implants (CIs). The aim of the new strategy is to obtain more natural sound in CIs by better mimicking the human auditory system. The new strategy was built in three independent stages as proposed in [6]. First a basilar membrane motion model was substituted by the filterbank commonly used in commercial strategies. Second, an inner hair cell model was included in a commercial strategy while maintaining the original filterbank. Third, both the basilar membrane motion and the inner-hair cell model were included in the commercial strategy. This paper analyses the properties and presents results obtained with CI recipients for each algorithm designed.
UnivIS-Import:2015-04-20:Pub.2007.tech.IE.aulab.zentr.anaudi